2007
DOI: 10.1111/j.1551-2916.2007.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Densification, and Phase Evolution Studies of Al2O3–Al2TiO5–TiO2 Nanocomposites and Measurement of Their Electrical Properties

Abstract: Alumina–aluminum titanate–titania (Al2O3–Al2TiO5–TiO2) nanocomposites were synthesized using alkoxide precursor solutions. Thermal analysis provided information on phase evolution from the as‐synthesized gel with an increase in temperature. Calcination at 700°C led to the formation of an Al2O3–TiO2 nanocomposite, while at a higher temperature (1300°C) an Al2O3–Al2TiO5–TiO2 nanocomposite was formed. The nanocomposites were uniaxially compacted and sintered in a pressureless environment in air to study the densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, many researches showed that grain refinement in alumina ceramics led to improved properties [10][11][12][13][14]. Fine-grained alumina matrix ceramics were considerably investigated and reported to possess superior properties compared to their conventional coarse-grained counterparts [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, many researches showed that grain refinement in alumina ceramics led to improved properties [10][11][12][13][14]. Fine-grained alumina matrix ceramics were considerably investigated and reported to possess superior properties compared to their conventional coarse-grained counterparts [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…The samples exhibited the maximum bulk density and minimum apparent porosity during sintering at 1300°C. Traditional Al 2 TiO 5 preparation techniques, such as reaction sintering of mechanically alloyed starting materials and solid-state reaction preparation routes, produce Al 2 TiO 5 at high temperatures ranging between 1400°C and 1500°C [23,24]. In the present study, the use of the sol-gel technique to prepare Al 2 TiO 5 powder enabled the production of nanosized powder, which in turn enhanced the densi cation of the produced bodies at a low sintering temperature of 1300°C.…”
Section: Densi Cationmentioning
confidence: 76%
“…And several investigations showed that a smaller grain size (grain refinement) in alumina ceramics led to improved mechanical properties [5,[18][19][20][21][22]. The mechanical strength of Al 2 TiO 5 ceramics also increased as the grain size decreased [23].…”
Section: Introductionmentioning
confidence: 93%